2018
DOI: 10.1521/pedi_2017_31_322
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship Between DSM-5 Personality Disorder Domains and Facets and Aggression in an Offender Population Using the Personality Inventory for the DSM-5

Abstract: This study explored associations between aggression and the Personality Inventory for the DSM-5 (PID-5) domains and facets in 208 male offenders. Regression analyses revealed no significant domain-level relationships using either the APA-three facets only (Krueger, Derringer, Markon, Watson, & Skodol, 2013) or the Krueger, Derringer, Markon, Watson, and Skodol (2012) scoring algorithms. The PID-5 facets of Hostility and Risk Taking were significantly associated with aggression. These findings highlight the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 84 publications
3
24
0
Order By: Relevance
“…The present study comprised part of a larger program of research designed to investigate correlates of aggressive behavior, PD traits, and aggression‐related cognitive constructs and emotional states in offenders (Dunne, Gilbert, & Daffern, ).…”
Section: Methodsmentioning
confidence: 99%
“…The present study comprised part of a larger program of research designed to investigate correlates of aggressive behavior, PD traits, and aggression‐related cognitive constructs and emotional states in offenders (Dunne, Gilbert, & Daffern, ).…”
Section: Methodsmentioning
confidence: 99%
“…A growing body of empirical research has found support for the psychometric properties of the PID-5. Specifically, the PID-5 has demonstrated acceptable internal consistency (Dunne et al, 2018; Gutierrez et al, 2017) and cross-cultural replicability of the five-factor structure (De Clercq et al, 2014; Quilty et al, 2013; Somma et al, 2019; Wright et al, 2012). The PID-5 has demonstrated convergence with alternative personality models and measures (Anderson et al, 2013; De Clercq et al, 2014; Hopwood et al, 2013; Watson et al, 2013); however, mixed findings regarding discriminant validity have been noted (Crego et al, 2015; Crego & Widiger, 2016; Quilty et al, 2013; Yalch & Hopwood, 2016).…”
mentioning
confidence: 99%
“…The PID-5 has demonstrated convergence with alternative personality models and measures (Anderson et al, 2013;De Clercq et al, 2014;Hopwood et al, 2013;Watson et al, 2013); however, mixed findings regarding discriminant validity have been noted (Crego et al, 2015;Crego & Widiger, 2016;Quilty et al, 2013;Yalch & Hopwood, 2016). Criterion validity has been established by research demonstrating support for expected associations between PID-5 traits and ratings of DSM-IV/DSM-5 PD categorical diagnoses (Anderson et al, 2014;Hopwood et al, 2012), as well as relevant clinical outcomes, such as aggression, antisocial behavior, and substance abuse (Dunne et al, 2018;Maples et al, 2015).…”
mentioning
confidence: 99%
“…Among female offenders, numbers are lower but still demonstrate the severity of the problem, as 42% have PDs and 21% have antisocial PD (Fazel & Danesh, 2002). In conclusion, there is a substantial association between aggression and personality dysfunctions, which include distorted perception of emotions and intentions of other people (Dunne, Gilbert, & Daffern, 2018a, 2018b; Reardon, Tackett, & Lynam, 2018).…”
mentioning
confidence: 99%